(untitled) (Indian Journal of Nematology, 2024)
A survey on plant parasitic nematodes of the order Tylenchida, superfamily Criconematoidea and subfamily Criconematinae revealed the presence of a new species of the genus Ogma Southern 1914 associated with the fibrous roots of Thatch grass from Zemabauk, Aizawl district of Mizoram, India. Ogma mizoramensis n. sp. is reported as a new species. This species is characterized by retrorse body annuli with eight rows of scales arranged longitudinally at the mid-body region with teeth or fringe-like structure at the posterior margin. The head consists of two annuli, the first annuli greater than the second annuli in width. True sub-median lobes absent. Stylet long and slender with an anchor-shaped basal knob. Vulva closed type with two conical projections at the anterior vulval lip. Tail short with pointed terminus. Body length = 0.29‒0.35 mm, stylet length = 75.7‒80.4 µm, R = 79‒80, RV = 11‒12, RVan = 3‒4, Ran = 7‒9, Roes = 21‒23, V = 86‒87% and VL/VB = 1.3‒1.5. Detailed morphological characterization, data along with their host, location, SEM images, and illustration are provided.